Implementation of prophylactic HPV vaccination: progress and future challenges. (September 2010) - Brabin, Loretta; Kitchener, Henry C; Stern, Peter L
Two licensed vaccines designed to prevent certain human papillomavirus (HPV) infections are currently available. Their use to prevent cervical cancer has depended on data from clinical trials of safety, immunogenicity and efficacy in preventing surrogate end points of cancer. Following these pivotal studies, HPV vaccines are being introduced into national vaccination programs, mostly in developed countries, and are largely targeting girls 10–14 years of age, with a one-time catch-up opportunity for older teens. Some countries have achieved a level of coverage that is consistent with economic models predicting their cost–effectiveness. At the same time, clinical trials among males and older women have led to pressure to expand the population groups offered HPV vaccination. Over the next 5 years, health authorities will need to make clear decisions about how best to deploy HPV vaccines, as well as to increase or maintain high coverage among young adolescent girls.